Effects of Oral Supplementation of Pomegranate Peel Extract on Some serum biochemical Parameters Related with Bone in Rabbit - Dilyar A Baban; Rezan M Omer; Sarchil E Mohyadeen (College of Dentistry/ University of Baghdad, 2019)
Background and aim: Pomegranate is a medicinal herb that can promote healing of periodontal tissue through differentiation of mesenchymal cells both in vivo and in vitro. Therefore, this study is to investigate the effect of oral supplementation of Punicagranatum L. peel extract on bone defect in rabbit. Methods: Forty five male rabbits were divided into 3 groups; group 1; baseline group(5 rabbits) left without bone defect. Group 2; study group (20 rabbits) with bone defect model that received daily 1ml of oral supplementation of pomegranate peel extract (PoPx). Group 3; control group (20 rabbits) with bone defect model that received distilled water. Bone defect was done into facial plate of lower right central incisor. Blood biopsies by cardiocentesis at times (base line, 3h, 1, 3 and 7days) for estimation of serum calcium, phosphorous, and vitamin D levels. Results: The results showed a significant increase in serum calcium and phosphorous levels only after 3 hours and 1 day of bone defect, in rabbits receiving water and rabbits receiving pomegranate peel extraction. Serum vitamin D level shows significant increase in all time intervals reaching maximum value after three days in rabbits receiving pomegranate peel extract, while no significant change was observed in rabbits receiving water. Conclusions: Supplementation of pomegranate peel extract can increase vitamin D absorption, thus it may promote the bone healing process.